2003
DOI: 10.1038/sj.sc.3101487
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of exercise participation in individuals with spinal cord injury: effects on quality of life, stress and pain

Abstract: Study design: Follow-up study of seven individuals with spinal cord injury (SCI) who completed a 9-month randomized control trial (RCT) of exercise training. Objective: In a 9-month RCT conducted in our lab, individuals with SCI who participated in a twice-weekly supervised exercise training reported greater perceived quality of life (PQOL), and less stress and pain than a nonexercising control cohort. The present follow-up study examined the voluntary continuation of exercise training after the study ended an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
56
0
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 112 publications
(66 citation statements)
references
References 12 publications
7
56
0
3
Order By: Relevance
“…There is evidence in support of this; Ditor et al 17 reported a significant drop in adherence rates from 80.6% to 42.7% 3-month following a 9-month training study, where participants were invited to continue exercising at the same facility but were not monitored in the same way as during the intervention period. The high adherence rate in the PAG group can also be attributed to the fact that participation eliminated some of the most commonly reported barriers to exercise participation in the SCI population: knowledge about exercise, facility and equipment accessibility, and personal support.…”
Section: Discussionmentioning
confidence: 79%
“…There is evidence in support of this; Ditor et al 17 reported a significant drop in adherence rates from 80.6% to 42.7% 3-month following a 9-month training study, where participants were invited to continue exercising at the same facility but were not monitored in the same way as during the intervention period. The high adherence rate in the PAG group can also be attributed to the fact that participation eliminated some of the most commonly reported barriers to exercise participation in the SCI population: knowledge about exercise, facility and equipment accessibility, and personal support.…”
Section: Discussionmentioning
confidence: 79%
“…Recent work from our laboratory found that 9 months of twice-weekly exercise training in persons with SCI resulted in improvements in perceived QOL, but these improvements were gone by 3-months post-training. 11,12 Moreover, this posttraining decrease in perceived QOL paralleled a decrease in exercise adherence, suggesting that continued exercise adherence is essential for the maintenance of exercise-induced improvements in subjective wellbeing in persons with SCI. If these results are to be generalized to the literature on BWSTT, it becomes important that we understand the degree to which gains in functional ambulation are maintained once BWSTT ceases.…”
Section: Introductionmentioning
confidence: 89%
“…With an increase in regular activity, the possibility to improve the adverse health-related consequences of paralysis, such as adiposity, insulin resistance, carbohydrate tolerance, lipid profile, and psychological wellbeing may also exist [38][39][40][41][42][43][44]. The increased VO 2 for walking, above that of sitting and standing, is evidence that additional effort from the user is required to perform ambulation in the exoskeleton (i.e., the exoskeleton is not performing all of the work for ambulation).…”
Section: Discussionmentioning
confidence: 99%